'n Leesmoontlikheid van Jeanne Goosen se teks Louoond : die vrou as skrywer binne die Suid-Afrikaanse bestel - Viljoen, Erika Valeska (Rhodes University, Faculty of Humanities, School of Languages, 1989)
This thesis investigates the narrative strategies of Jeanne Goosen, as employed in her short novel, Louoond. I regard this text as an excellent example of modern Afrikaans prose, and particular reference was made to her previous novel: Om 'n mens na te boots which indicates similarities to the text under scrutiny. Chapter One is a close reading of the first chapter of the novel, in order to identify certain prominent codes, and also to determine what the text itself prescribes. My presumption is that the text determines how it should be read, that no single, predetermined strategy can be rigidly applied to it. Thus I formulated my own individual possible reading from the first chapter, and I view it throughout as mere "speculation", since this possible reading remains only a possibility. Chapter Two contains the theoretical background that is necessary for a scientific study of this kind. I followed mainly the strategies of Roland Barthes and Jacques Derrida, who are pioneers in the post -modernistic theory. It was particularly important to investigate the role of the narrator: the narrator in Louoond presents herself as a writer, therefore it is the process that is paramount. In Chapter Three the code of writing, as identified in Chapter ÊºOneÊº of Louoond, is followed closely throughout the text. In Louoond, which is metatextual, violence is textually inherent, and also part of the process of writing. This violence is definitely also part of the South African situation as it is signified in the novel. Throughout the narrator is in a state of tension about her own role in the ÊºrevolutionÊº - in which also her own text is a revolution in language, but always within the NOW of South Africa. Chapter Four concerns itself mainly with the role of the woman as narrator, as muse, as primary protagonist. I discuss the code of woman in relation to prominent feminist writers, but it remains in context of the text. Each issue is in the first place determined by the text, the text therefore determines which feminist issues will be investigated. The South African situation, and specifically the Afrikaner situation, serves throughout as intertext for Louoond, as with the code of writing. Other intertextual references are important, because the text is never independent from anything outside itself, and could not exist in such independence. Music plays an important role, with Callas as muse and as fellow female artist, while George Sand functions as fellow writer. Woman, independent of man, is put forward as creator. In my reading, the text remains in the first place a fabrication/imitation of the South African reality, and the fInal scene reaffirms the Êºfinal catastropheÊº that is indicated in the motto as a Êºcondition of controlled hysteriaÊº
Keywords: Goosen, Jeanne -- Criticism and interpretation; Goosen, Jeanne -- Louoond